Program Urban Farming sebagai Usaha Pemanfaatan Lahan Pekarangan untuk Ketahanan Pangan Lokal Masyarakat Karimunjawa - Sriyanto; Banowati, Eva; Kurniawan, Edi; Amrullah, Fikri; Al-Hanif, Ervando Tommy (Universitas Dinamika, 2025)
This activity aims to improve the welfare and food security of the Karimunjawa community through the concept of urban farming. Urban farming is an agricultural approach that can be applied in urban and rural areas to increase local food availability, strengthen community involvement in food production, and create a sustainable environment. This activity is implemented through a participatory approach with a focus on empowering village women and youth to utilize their yards to produce vegetables and fruits independently. A series of socialization, training, and mentoring were conducted to equip the community with skills in urban farming practices, including farming techniques in limited land (polybags), managing organic waste into compost, and applying simple technology to increase agricultural yields. The results showed an increase in community skills in farming, with a number of families successfully producing food for their own consumption. The evaluation was conducted through surveys, interviews, and observations to measure the improvement of knowledge, skills, and cultivation practices. The evaluation results showed that most of the participants were able to apply the cultivation techniques well and began to feel the economic benefits and more secure food availability. The sustainability of this program is supported by the formation of local farmer groups and community networks that can continue to exchange experiences and support the development of urban farming at the village level.